2019
DOI: 10.1101/860882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Females don’t always sing in response to male song, but when they do, they sing to males with higher pitched songs

Abstract: The long-held view that bird song is exclusively a male trait has been challenged recently by a number of studies and reviews highlighting the prevalence of female song. In spite of that, there remains a lack of knowledge on the function of female song, with most evidence thus far focusing on females performing duets with males in courtship displays, typically for joint territory defence or mate guarding purposes. Here we show in a tracheophone suboscine passerine Formicarius moniliger, a sexually monomorphic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 58 publications
5
6
0
Order By: Relevance
“…Male magpie-larks are usually larger than females and are generally more aggressive which may drive females to do this (Hall, 1999). A similar finding was found in another species, the Mexican antthrush, Formicarius moniliger (Kirschel et al, 2019): while females were less likely to respond to male playback compared to female playback, when they did respond to male playback they sang at a higher frequency. They hypothesised this may be to reduce the likelihood of physical conflict with rival of a large body size.…”
Section: Ta B L Esupporting
confidence: 68%
See 1 more Smart Citation
“…Male magpie-larks are usually larger than females and are generally more aggressive which may drive females to do this (Hall, 1999). A similar finding was found in another species, the Mexican antthrush, Formicarius moniliger (Kirschel et al, 2019): while females were less likely to respond to male playback compared to female playback, when they did respond to male playback they sang at a higher frequency. They hypothesised this may be to reduce the likelihood of physical conflict with rival of a large body size.…”
Section: Ta B L Esupporting
confidence: 68%
“…Male magpie-larks may also represent a stronger territorial threat than females, since previous studies (but not the current study) found higher song initiation rates to male than female playback by male magpie-larks (Hall, 2000;Hall & Magrath, 2000;Mulder et al, 2003). Sex-specific responses have often been recorded in song rate (Appleby et al, 1999;Arcese et al, 1988;Cain & Langmore, 2015;van den Heuvel et al, 2014), but the current study is one of the first, to our knowledge, to show frequency changes as a sex-specific response (see Kirschel et al, 2019).…”
Section: Ta B L Esupporting
confidence: 44%
“…This brings us to the hypothesis that the frequency of acoustic signals may be sexually selected, if frequency acts as an indicator of an individual’s size, dominance or fighting ability. In various taxa, the frequency of male vocalisations indeed seems to indicate individual body size and can influence territory establishment (or other forms of male − male competition), attractiveness (female choice, based on the ability to discern male size differences by vocal frequency) and ultimately an individual’s reproductive success (Morris and Yoon, 1989; Apicella et al ., 2007; Charlton et al ., 2007; Hardouin et al ., 2007; Vannoni and McElligott, 2008; Forstmeier et al ., 2009; Brumm and Goymann, 2017; Kirschel et al ., 2020). Thus, if low‐frequency sounds are advantageous in inter‐ and intrasexual interactions (Davies and Halliday, 1978; Wagner, 1989; Briefer et al ., 2010; Bro‐Jørgensen and Beeston, 2015; but see Fischer et al ., 2004), we predict correlated evolution of male vocal frequency and indices of the intensity of sexual selection such as male‐biased sexual size dimorphism (Trivers, 1972; Fairbairn, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…With this shifting view, new questions arise regarding the function of female song and the selection pressures underlying sexual differences (Riebel et al 2019). Even though the study of female song represents a very small fraction of the bird song literature (Odom and Benedict 2018), there is growing evidence, from an increasing number of species, that female song serves a variety of functions such as territory advertisement (Cooney and Cockburn 1995;Cain et al 2015), mate attraction (Langmore et al 1996), mate guarding (Reichard et al 2018), or resource defense (Tobias and Seddon 2009) during inter-or intrasexual interactions (Krieg and Getty 2016;Kirschel et al 2020). In non-duetting species, one of the most common functions of female song reported to date is related to the competition for breeding resources (and mates) between females (Langmore 1998;Austin et al 2021).…”
Section: Introductionmentioning
confidence: 99%